Contribution of CMR and MDI to the picture of the hearing system selectivity - Jorasz, U. (Archives of Acoustics, 2001)
The general picture of the hearing system selectivity should take into account the involving of the peripheral and central mechanisms. Everything what is known about CMR and MDI can contribute to the formation of auditory scene and take the important place in this picture.